Land subsidence estimation using DinSAR method ALOS PALSAR image in Padang City West Sumatra, Indonesia - Rahmi Sukmawati; Mirza Muhammad Waqar; - Syafriani; - Yohandri; Joshapat T. Sri Sumantyo (PILLAR OF PHYSICS, 2021)
Land subsidence is a phenomenon that occurs in big cities around the world and in Indonesia. Padang as one of the largest cities in West Sumatera also facing land subsidence due to natural phenomena and human induced. Padang City is located at the west coast of Sumatera Island which is the junction point of three active plates that cause frequent earthquakes. Main goals of this research are to know the distribution of area affected by land subsidence, to know the estimated value of land subsidence and to know the value of the velocity of land subsidence in Padang area using DInSAR method. The data used in this study is ALOS PALSAR Image Level 1.1 of Padang city during 2007 to 2010 was obtained through JMRSL CERES Chiba University, Japan and collected through Alaska Satellite Facility website. Differential Interferometric Synthetic Aperture Radar (DInSAR) is a technique considered to be one of the most efficient technique for detecting land subsidence. The DInSAR method is used in mapping altitude changes developed into a land-subsidence map each year. The mapping results show the distribution of the areas affected by the maximum land subsidence in Padang area of West Sumatera are Padang Utara, Nanggalo, and Padang Barat Subdistricts. The land subsidence insignificant occurred is Padang Selatan and Lubuk Begalung Subdistricts. The estimated value of the land subsidence distribution in Padang area using DInSAR method has decreased significantly after the earthquake of September 30, 2009 in Padang Utara, Nanggalo and West Padang Subdistricts is around 0 - 32.70 cm, and the value of land subsidence velocity is around 0.13 - 12 cm/year. One of the expected effects of land subsidence can be increased in the area susceptible for flooding in Padang city.